Implementation Strategy of Mutaba'ah in Improving Santri's Memorization in Madrasah Al-Qur'an Da'wah and Entrepreneurship at Merapi Merbabu Islamic Community Boarding School - Yani; Siti Rohimah (Didaktika: Jurnal Kependidikan, 2024)
The aim of this research is to find out the extent of the strategy of implementing mutaba'ah in an effort to increase the memorization of students in madrasah al-Qur'an Da'wah and entrepreneurship in Islamic boarding schools in the Merapi Merbabu community. This research uses a qualitative approach. The subjects of this research were the students of MAQDA PM3 Windusajan, Wonolelo, Magelang, which is an educational unit under the auspices of the Merapi Community Islamic Boarding School Foundation. This research was carried out from October to December 2023. Meanwhile, the informants in this research were the Head of MAQDA, ustadz tahfidz and santri. The data in this research was obtained through observation, structured interviews and documentation as well as relevant literature results. Data analysis uses the Miles and Huberman analysis model called interactive analysis. This analysis is divided into several stages: data collection, data reduction, data presentation, and drawing conclusions. The results show that the strategy used to memorize is the mutaba'ah sheet which is divided into two, namely the muroja'ah activity sheet and the ziyadah activity sheet. This mutaba'ah sheet is filled in by the students and then submitted to the musyrif tahfidz and controlled by the ustadz tahfidz as the coordinator of the tahfidz program at MAQDA PM3. Meanwhile, the supporting factors are the students' interest in talent and the students' motivators who come from the musyrif and the students' parents. The inhibiting factor is lack of discipline. Then, as a result of the mutaba'ah strategy, the average student is able to meet the normal criteria of 2.5 to 3 jars per semester and some students are able to exceed this normal achievement.